Non-intubated uniportal VATS surgery is feasible approach - AlGhamdi, Zeead M.; Ahn, Seha; Kim, Kwan-Chang; Sung, Sook-Whan (Journal of Thoracic Disease; Vol 12, No 3 (March 23, 2020): Journal of Thoracic Disease, 2019)
Innovation is a fundamental part of human development, and thoracic surgery is part of this developmental process. Enhancing the surgical experience of the patient was always the motive for thoracic surgeons to provide the safest and more convenient surgical procedure to the patient with fast hospital recovery and with less pain and trauma.